2013
DOI: 10.1111/ijfs.12428
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive compounds, in vitro antioxidant capacity and Maillard reaction products of raw, boiled and fried garlic (Allium sativum L.)

Abstract: Summary Garlic is used in many dishes but some of its bioactive compounds are lost when exposed to heat. This study evaluated bioactive compounds, antioxidant activity and Maillard reaction products of raw (RG), boiled (BG) and fried garlic (FG). Total phenolic compounds, flavonoids, allicin and phytosterol were quantified as well as dietary fibres and mineral content. Antioxidant activities of RG, BG and FG were evaluated by oxygen radical absorbance capacity (ORAC), oxidation of β‐carotene/linoleic acid and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 37 publications
1
19
0
Order By: Relevance
“…frying showed a more decrease than others, caffeic acid was much easier to be reduced than chlorogenic acid or other phenolic acids). In addition to the degradation during cooking, the transport from the tissue to the surrounding water and the amount that taking part in the Maillard reaction will cause a further loss of content (de Queiroz et al, 2014).…”
Section: Effect Of Cooking Treatments On Phenolic Acidsmentioning
confidence: 99%
“…frying showed a more decrease than others, caffeic acid was much easier to be reduced than chlorogenic acid or other phenolic acids). In addition to the degradation during cooking, the transport from the tissue to the surrounding water and the amount that taking part in the Maillard reaction will cause a further loss of content (de Queiroz et al, 2014).…”
Section: Effect Of Cooking Treatments On Phenolic Acidsmentioning
confidence: 99%
“…Although volatile compounds are of outmost importance, especially organosulfuric compounds such as thiosulfinates, garlic bulbs contain a great variety of other bioactive compounds which contribute to their overall antimicrobial activity, including phenols, saponins, peptides and so forth (Kyung, 2012;Lanzotti, Barile, Antignani, Bonanomi, & Scala, 2012;Lanzotti et al, 2013), especially after processing of garlic. It has been reported that processing treatments may alter chemical composition and therefore affect significantly antimicrobial and antioxidant properties of garlic products, mostly due to the labile nature of organosulfuric compounds (de Queiroz et al, 2014;Horita et al, 2016). Therefore, garlic bulbs content in other bioactive compounds except for organosulfuric ones, is essential for their overall antimicrobial properties.Total phenolic compounds content of garlic bulbs shows a great variability depending on both growing condition and genetic factors.…”
Section: Introductionmentioning
confidence: 99%
“…Garlic, well known as a healthy, therapeutic spices and seasonings in virtually every cuisine in the world, possesses multiple beneficial properties that enhances antimicrobial (Pirak et al, 2012), antithrombotic (Ariga & Seki, 2006) and antioxidant activities (Kim et al, 1997;Queiroz et al, 2014). Biological functions are also improved with consumption of garlic by lowering serum lipid, glucose levels and blood pressure (Corzo-Mart ınez et al, 2007;Kim et al, 2014a).…”
Section: Introductionmentioning
confidence: 99%